Identification and Cloning of Genes from Porphyromonas gingivalis after Mutagenesis with a Modified Tn4400 Transposon from Bacteroides fragilis - Chen, Tsute (American Society for Microbiology, 2000)
Porphyromonas gingivalis is a gram-negative, black-pigmented, oral anaerobe strongly associated with adult periodontitis. Previous transposon mutagenesis studies with this organism were based on the Bacteroides transposon Tn4351. Characterization of Tn4351-disrupted genes by cloning has not been an efficient way to analyze large numbers of mutants and is further complicated by the high rate of cointegration of the suicide delivery vector containing Tn4351. In this study, we mutagenized P. gingivalis with a modified version of the Bacteroides fragilis transposon Tn4400. Plasmid pYT646B carrying the transposon was mobilized from Escherichia coli to P. gingivalis ATCC 33277 by conjugation. Both normal and inverse transposition frequencies were similar (3 × 10(−8)). However, the inverse transposon (Tn4400′) contains a pBR322 replicon and a β-lactamase gene; thus, the cloning of disrupted genomic DNAs from inverse transposition mutants was easily accomplished after ligation of genomic fragments and transformation into E. coli. Thousands of transconjugants could be obtained in a single mating experiment, and inverse transposition was random as demonstrated by Southern hybridization. By this procedure the disrupted genes from P. gingivalis pleiotropic mutants were quickly cloned, sequenced, and identified.